Voluntourism: Can universities shape the present into a future? - Rodrigues, H.; Abreu, C. (Journal of Marketing for Higher Education, 2025)
The Voluntourism (VT) phenomenon combines volunteering with travelling. Students’ education as global citizens challenges universities for community-engagement programs to enrich participants’ personal and professional development. The present article addresses the issue of how universities can retransform VT into a win-win scenario based on co-creation experiential learning programs. A lexical analysis of 28 semi-structured interviews reveals universities’ positive influence on the progress of the VT industry by extending their mission toward the inclusion of communities. The findings reported here advance an opportunity together with VT operators’ operational support that goes beyond knowledge transference while embracing a mutual education in socio-cultural skills for students as volunteers and local communities.